Decellularized Human Gut as a Natural 3D Platform for Research in Intestinal Fibrosis. Issue 11 (14th June 2019) - Giuffrida, Paolo; Curti, Marco; Al-Akkad, Walid; Biel, Carin; Crowley, Claire; Frenguelli, Luca; Telese, Andrea; Hall, Andrew; Tamburrino, Domenico; Spoletini, Gabriele; Fusai, Giuseppe; Tinozzi, Francesco Paolo; et al.
Abstract: Background: The current methodologies for the identification of therapeutic targets for inflammatory bowel disease (IBD) are limited to conventional 2-dimensional (2D) cell cultures and animal models. The use of 3D decellularized human intestinal scaffolds obtained from surgically resected intestine and engineered with human intestinal cells may provide a major advancement in the development of innovative intestinal disease models. The aim of the present study was to design and validate a decellularization protocol for the production of acellular 3D extracellular matrix (ECM) scaffolds from the human duodenum. Methods: Scaffolds were characterized by verifying the preservation of the ECM protein composition and 3D architecture of the native intestine and were employed for tissue engineering with primary human intestinal myofibroblasts for up to 14 days. Results: Engrafted cells showed the ability to grow and remodel the surrounding ECM. mRNA expression of key genes involved in ECM turnover was significantly different when comparing primary human intestinal myofibroblasts cultured in 3D scaffolds with those cultured in standard 2D cultures on plastic dishes. Moreover, incubation with key profibrogenic growth factors such as TGFβ1 and PDGF-BB resulted in markedly different effects in standard 2D vs 3D cultures, further emphasizing the importance of using 3D cell cultures. Conclusions: These results confirm the feasibility of 3D culture of human intestinal myofibroblasts in intestinal ECM scaffolds as an innovative platform for disease modeling, biomarker discovery, and drug testing in intestinal fibrosis. Abstract : We successfully developed a novel and reproducible protocol designed to "decellularize-recellularize" acellular 3D extracellular matrix (ECM) scaffolds from human intestine. 3D cultures of intestinal myofibroblasts in ECM scaffolds represent a key alterative to 2D cultures on plastic and animal models.